Influences of COVID-19 vaccination policy on students’ vaccine acceptance - Thuli G. Mthembu; Samantha Harrison; Kauthar Botha; Jessica Britz; Brittney Katts; Michaela Millar; Zia Sulliman; Vutlhari Zitha (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2023)
Background: Higher education institutions (HEIs) developed and implemented a mandatory COVID-19 vaccination policy to facilitate vaccine acceptance and vaccination among universities’ staff and students. However, little is known about influences of the mandatory vaccination policy on health science students at a university and they tend to result in vaccine hesitancy.